Association between BMI and health-related physical fitness: A cross-sectional study in Chinese high school students - Qin, Guoyang; Qin, Yong; Liu, Bin (Frontiers in Public Health, 2022)
Background: Existing studies reporting on the levels of physical fitness among high school students use relatively few fitness tests for indicators of physical fitness, thus, incomprehensively evaluating the levels of physical fitness. This study aimed to investigate the cross-sectional association between Chinese high school students' body mass index (BMI) and their physical fitness index (PFI) using five fitness indicators. Method: Anthropometric measurements and indicators from five measures of physical fitness (50-m sprint, sit and reach, standing long jump, 800/1000-m run, pull-up/bent-leg sit-up) were assessed. BMI was calculated to classify individuals into underweight, normal weight, overweight, and obese categories. Z-scores based on sex-specific mean and standard deviation were calculated, and the sum of Z-scores from the six fitness tests indicated the PFI. The findings were fitted to a linear regression model to elucidate the potential relationship between BMI and PFI. Results: In total, 176,655 high school students in Jinan, China, completed the physical fitness tests between 2020–2021. The one-way ANOVA models showed that PFI in the normal category was significantly higher as compared to all the other BMI categories within both male and female groups (p < 0.001), and PFI in the obese category was significantly lower as compared to all the other BMI categories for both male and female groups (p < 0.001). The association between PFI and BMI showed an inverted U-shape relationship. Conclusions: This study demonstrated that BMI affects the PFI in both males and females. As compared to the obese and overweight categories based on BMI, significantly higher scores of PFI were observed for males and females.